Understanding love and intimacy through the constructions of young gay men - Prado-Castro, Daniela Maria (My University, 2017)
Intimacy and romantic love are influenced by the social context in which patterns of intimacy and attachment are learned, experienced or expressed. The social context is interlinked with culture, and sexuality. The study of masculinity has a strong link with gender as it unpacks a particular gendered identity. The current study aimed at unpacking the understanding of intimacy and romantic love amongst young gay men. This research examined data collected from three focus group discussions with a total of nine young gay men between the ages of 19 and 29 years. The participants were located through purposive and snowball sampling. The information gathered during the focus group discussions was analysed using thematic content analysis. Using critical masculinity theory, this research explores the different definitions of intimacy, the relation between the social space or the location and the expression of intimacy, and the intersections of homosexuality and intimacy. In addition, the need for alternative representations of homosexuality were identified, namely the need for new depictions of homosexuality in the media. The results of the study indicated two distinct patterns in relation with the expression of intimacy amongst gay men. Firstly, participants attempted to replicate hegemonic masculinity in their intimate and romantic relationships. Secondly, there is a strong desire to break away from hegemonic masculinity and construct new ways of expressing their homosexual identity, their masculinity and, in turn, intimacy. Finally, the research concludes by highlighting that intimacy amongst gay men is directly influenced by developmental patterns of masculinity in society that intersect with socio-economic status, race and culture, and gender.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Arts in Community-based Counselling Psychology, 2017
Keywords: Young gay men--South Africa--Social conditions; Male homosexuality--South Africa; Gender expression--South Africa; Masculinity--South Africa